Development of a Rice Combine Harvester Instrumentation System for Mapping of Crop Yield and Field Performance - Yap, Yoke Kin (2006)
Yield variations within a paddy field indicate the loss of potential of valuable cultivated land in Malaysia. By integrating the location in the field of a combine harvester with accurate yield measurement, it is possible to produce a map with detailed, site-specific variations. When this yield map is used in conjunction with soil maps, topographic maps and weed maps, it is possible to understand the reasons for yield variations. From these maps, treatment plans can be made to control inputs specific to a desired location, using variable rate controllers to optimize the use of land in order to achieve maximum yield. Thus, this research was initiated to develop a dedicated and complete instrumentation system on-board a New Holland TC-56 rice combine harvester to monitor the grain losses, harvested crop yield and combine operating parameters during harvesting operation with the ultimate goal of generating grain loss map, crop yield map and combine field performance parameter maps. The developed instrumentation system has been installed with ultrasonic displacement sensor for measurement of combine actual cutting width and the header position sensor for measurement of header cutting height position. Grain flow, grain moisture and grain loss sensors have been installed and calibrated for measurements of grain flow in kg/m2, percentage of grain moisture contents and grain losses in grams during harvesting, respectively. Radar velocity sensor and theoretical ground speed sensor have been used to measure the actual ground speed, theoretical ground speed of the combine in the field during operation, respectively. The tilt sensor has been used to measure the pitch and roll angles of the combine in the field during operation. In order to measure the combine engine fuel consumption, fuel flow sensor has been used. Resistance strain gauge and a slip ring have been used to measure the combine drive axle shaft torque during operation. The data acquisition system is used for conditioning, amplifying, collecting, processing, displaying and storing all the measured parameters from the sensors and differential global positioning system receiver. The differential global positioning system is used for identifying the geo-position of combine in the field. Laboratory Virtual Instrument Engineering Workbench (LabVIEW) software is used to control and process the outputs from different sensors in the data acquisition system. The LabVIEW has also been used for data logging, monitoring, processing and storing of the performance signals from sensors and collected differential global positioning system signal. The functionality and reliability of the developed instrumentation system has been tested in a harvesting operation with the combine harvester at a paddy field plot located in Sawah Sempadan Block C, Kuala Selangor under the North West Selangor Agricultural Development Project authority. Point data with specific location collected continuously with an interval of one second over the field area were down loaded into computer and presented into a spatial map using ArcGis 8.3 software.